The challenge of tobacco control at a university hospital - Natália Ferreira Cruz; Vanessa Monteiro Mantovani; Sérgio Von Poser Maciel; Solange Klockner Boaz; Marli Maria Knorst; Isabel Cristina Echer
Objective: To identify the actions taken by the Commission of Tobacco Control (CTC) to control smoking in the hospital environment.Methods: Descriptive and exploratory retrospective documentary research conducted at a university hospital in southern Brazil, in 2014. The content of the minutes of CTC meetings was used to create a database, and the rounds reports were descriptively analyzed. We sought to identify the most relevant actions from 2005 to 2014.Results: The CTC implemented the Tobacco-Free Environment programme restricted cigarette smoking to designated areas and subsequently deactivated these areas. The only remaining outdoor smoking area in 2014 was deactivated.Conclusion: CTC actions have contributed to tobacco control in the hospital environment. This study will hopefully serve as a model to encourage other institutions to implement similar actions.